THE ECONOMICS OF REDD+ (REDUCING EMISSIONS FROM DEFORESTATION AND FOREST DEGRADATION): A POLICY ANALYSIS OF ITS IMPLEMENTATION IN INDONESIA - Judijanto, Loso; Jun, Wang; Mei, Chen (Journal of Selvicoltura Asean, 2025)
Reducing Emissions from Deforestation and Forest Degradation (REDD+) is a pivotal international climate change mitigation mechanism, with Indonesia being a key implementing country due to its vast tropical forests. Despite significant international investment, the economic viability and effectiveness of REDD+ in achieving its goals are contingent upon the design and implementation of national policies. This study aimed to conduct a comprehensive economic policy analysis of REDD+ implementation in Indonesia, evaluating its efficiency, cost-effectiveness, and the equity of its benefit-sharing mechanisms. A policy analysis framework was employed, integrating economic principles with a review of national and sub-national REDD+ policies, regulations, and project implementation documents from 2010 to 2024. The analysis was supplemented by a meta-synthesis of financial reports from REDD+ pilot projects and existing academic literature to assess transaction costs, financial flows, and benefit distribution. The analysis reveals significant economic challenges. High transaction costs, coupled with unclear carbon tenure and property rights, have created substantial inefficiencies and deterred private sector investment. Furthermore, the absence of a consistent national carbon price has undermined the financial incentives for land-use change. Benefit-sharing mechanisms were often found to be ad-hoc, leading to inequitable outcomes that failed to adequately compensate local communities for their opportunity costs. For REDD+ to become an economically viable and effective climate mitigation strategy in Indonesia, significant policy reforms are imperative. Future policies must focus on reducing transaction costs, providing clear and secure carbon tenure, and establishing transparent, equitable, and efficient benefit-sharing mechanisms that reflect the true costs borne by local stakeholders.